SUSPENSE AND ITS CLASSIFICATION IN MODERN ENGLISH LINGUISTICS - Kemertelidze, Nino; Manjavidze, Tamar (European Scientific Journal, ESJ, 2013)
Text analysis, especially linguo-stylistic analysis of a text is one of the most important issues in modern linguistics. It is a well-known fact that stylistic devices play the greatest role in text analysis. Among other figures of speech, suspense is one of the widely used syntactic stylistic devices. The given article discusses peculiarities of suspense and identifies the classes of this very interesting stylistic device in modern English linguistics.